Ortner’s syndrome with left vocal cord paralysis secondary to thoracic aortic aneurysm: A case report - ชุติมา ไพบูลย์ (Thai Journal of Otolaryngology Head and Neck Surgery, 2023)
Ortner’s syndrome or cardiovocal syndrome is a rare condition caused by compression of the left recurrent laryngeal nerve (RLN) by thoracic aortic aneurysm. We report a case of a 78-year-old Thai female who had been complaining of hoarseness of voice for 2-3 weeks. Physical exam demonstrated evidence of left vocal cord paralysis without any suspicious mucosal lesions or palpable neck mass. Initial work up with chest radiograph showed a lobulated soft tissue mass at left superior mediastinum which was subsequently found to be a 6.7-cm saccular aneurysm with mural thrombus and extending into aortopulmonary window on chest CT scan. The aneurysm compressed the expected course of the left RLN, resulting in left vocal cord paralysis. She underwent thoracic endovascular aortic repair (TEVAR). In advanced age patients with hoarseness, aside from malignancy, rare but potentially life threatening causes such as Ortner’s syndrome should also be considered in the differential diagnosis. Abbreviations: RLN = Recurrent laryngeal nerve, TEVAR = Thoracic endovascular aortic repair, AP window = aortopulmonary window Keywords: Ortner’s syndrome, thoracic aortic aneurysm, recurrent laryngeal nerve, vocal cord paralysis.